2022
DOI: 10.3390/ijms231911389
|View full text |Cite
|
Sign up to set email alerts
|

Overview of MicroRNAs as Diagnostic and Prognostic Biomarkers for High-Incidence Cancers in 2021

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs (ncRNAs) about 22 nucleotides in size, which play an important role in gene regulation and are involved in almost all major cellular physiological processes. In recent years, the abnormal expression of miRNAs has been shown to be associated with human diseases including cancer. In the past ten years, the link between miRNAs and various cancers has been extensively studied, and the abnormal expression of miRNAs has been reported in various malignant tumors, such as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 152 publications
0
13
0
Order By: Relevance
“…Breast ultrasound is used as an auxiliary exam, but it depends on equipment, subjective interpretation and can lead to false positives ( Majid et al, 2003 ). Additionally, other imaging-based approaches, including X-rays, computed tomography, and magnetic resonance imaging, are associated with an increased frequency of highly invasive biopsies to determine the malignant or benign nature of the tumor ( Zhang et al, 2022 ). Furthermore, some lesions can be highly variable with a probability of malignancy ranging from 3% to 95%, causing patients with benign lesions to undergo invasive examinations and, in some cases, surgery as the method of first choice, unnecessarily ( Giussani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Breast ultrasound is used as an auxiliary exam, but it depends on equipment, subjective interpretation and can lead to false positives ( Majid et al, 2003 ). Additionally, other imaging-based approaches, including X-rays, computed tomography, and magnetic resonance imaging, are associated with an increased frequency of highly invasive biopsies to determine the malignant or benign nature of the tumor ( Zhang et al, 2022 ). Furthermore, some lesions can be highly variable with a probability of malignancy ranging from 3% to 95%, causing patients with benign lesions to undergo invasive examinations and, in some cases, surgery as the method of first choice, unnecessarily ( Giussani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical significance of Cav1 stromal loss and its associated prognostic value in breast cancer has been known for some time and yet the mechanism of its loss remains unknown. Although there are multiple studies that have demonstrated the role of miRNAs in breast cancer and both their diagnostic and prognostic value ( 18 ), there are few linking the expression of a miRNA-mediated mechanism of Cav1 loss ( 19 , 20 ) and none that address the loss of Cav1 in the stromal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have emerged as promising candidates for diagnostic and prognostic biomarkers in high-incidence cancers like CRC, owing to their association with abnormal expression profiles across various malignancies. These molecular signatures offer potential utility in cancer screening and prognostic assessment, providing valuable insights into disease progression and patient outcomes [ 30 ]. One of the critical advantages of miRNAs lies in their remarkable stability and detectability in clinical tissue specimens.…”
Section: Reviewmentioning
confidence: 99%